Hacking Marketing Recovery Potential through the Educational Marketing Dimension Using a Fishbone Diagram - Agam Amintaha; Supriyono Supriyono; Sutono Sutono (Pusat Riset dan Inovasi Nasional, 2026)
This study is driven by the stagnation in student enrollment at a creative industry-based school that offers strong differentiation but has not effectively optimized its educational marketing strategy. The primary objective is to analyze the factors contributing to the stagnation and to develop a marketing recovery model grounded in educational marketing dimensions. The study utilizes a Fishbone Diagram to explore elements such as social media promotion, animation film works, facilities and infrastructure, and the curriculum. A descriptive qualitative approach is employed, utilizing in-depth interviews, observation, and documentation. The data analysis involves data reduction, data display, and conclusion drawing with cause-and-effect mapping. The results highlight that the primary cause of stagnation is the lack of synergy between the educational marketing dimensions. An integrative model that leverages creative differentiation is proposed as a strategic solution to revitalize marketing efforts and enhance student enrollment. This research provides actionable insights for improving the marketing strategy of the school.